Exploring the cost-effectiveness of Albumin-enhanced IV crystalloids in sepsis fluid resuscitation - Mohamed Metwally Mosly; Hesham Metwalli Mousli; Iman Mohamed Momtaz Ahmed; Mohamed Ibrahim Affify Abdou (Advances in Medical, Pharmaceutical and Dental Research, 2024)
Background:  This study aims to evaluate the cost-effectiveness of using albumin as well as crystalloids compared to the baseline use of crystalloids alone in the management of sepsis in the context of the Egyptian healthcare system. crucial for healthcare policymakers and managers, particularly in settings where reasonable cost containment is a priority. Methods: A decision tree model was created using TreeAge Healthcare Pro® software to compare two treatment groups for patients with severe sepsis or septic shock: one receiving only crystalloid fluids and the other receiving both crystalloid fluids and human albumin. The treatments were compared using the Incremental Cost-Effectiveness Ratio (ICER) and Net Monetary Benefit (NMB). Deterministic and probabilistic sensitivity analyses were conducted to assess the robustness of the results. Results: Although comparing the cost-effectiveness of both alternatives showed an ICER of 162,00 L.E in favor of the albumin plus crystalloids use in sepsis cases management, there was no dominance of either alternative over the other in terms of the cost-effectiveness plane.  By considering the NMB relevant to each individual alternative, the albumin plus crystalloids choice resulting in (-323,485 L.E) while the use of crystalloids alone resulting in higher NMB estimate of (-312,285 L.E). The results showed a considerable sensitivity to the cost of Albumin, the probabilistic sensitivity analysis showed robustness of the base case results over the estimated willingness to pay threshold of 160,000 L.E. Conclusions: The study showed that albumin-based management of sepsis and septic shoch patients is not a cost-effective choice up to the WTP threshold of 300,000 L.E.   Received: 04 July 2024 Accepted: 26 August 2024 Published: 19 September 2024